(untitled) (Journal of Eye Movement Research, 2018)
Direct comparison of results of humans and monkeys is often complicated by differences in experimental conditions. We replicated in head unrestrained macaques experiments of a recent study comparing human directional precision during smooth pursuit eye movements (SPEM) and saccades to moving targets (Braun & Gegenfurtner, 2016). Directional precision of human SPEM follows an exponential decay function reaching optimal values of 1.5°-3° within 300 ms after target motion onset, whereas precision of initial saccades to moving targets is slightly better. As in humans, we found general agreement in the development of directional precision of SPEM over time and in the differences between directional precision of initial saccades and SPEM initiation. However, monkeys showed overall lower precision in SPEM compared to humans. This was most likely due to differences in experimental conditions, such as in the stabilization of the head, which was by a chin and a head rest in human subjects and unrestrained in monkeys.